Ամենայն Հայոց կաթողիկոս Ղուկաս Կարնեցու նամակագրությունը հնդկահայ գործիչների հետ (XVIII դ. վերջ) - Ամիրջանյան, Հասմիկ Հ. (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Переписка католокоса Гукаса Карнеци с видним армянскими деятелям Индии, архиереями, содержит богатый материал для изучения социально-экономической ситуации Первопрестольного св. Эчмиадзина, духовной жизни армянской епархий Индии, политической ситуации Восточной Армении и т.д. В некоторых письмах обсуждаются вопросы национально-освободительного движения армянского народа и освобождении Армении от турецко-персидского иго. В письмах выражены разнообразия политических взглядов разных армянских деятелей, их переживания и отношение к политическим и религиозным проблемам армянского народа. Письма интересны для изучения национально-освободительного движения армянского народа. Письма отражают также деятельность Католикоса Всех армян в деле образования и книгопечатия. Во время предводительства Гукас Карнеци упад и подъем школы в Св. Эчмиадзине были обусловлены целым рядом внутренних и внешних факторов. В этот период создание культурно-просветительских учреждений сталкивалось с трудностями из-за многочисленных экономических, социальных и политических проблем. Переписка содержит богатый материал также для изучения строительной деятельности Карнеци. Основные строительные расходы были покрыты известными армянами Индии. Армянская община Индии также финансировала строительство кафедрального собора Св. Эчмиадзин. The correspondence of Catholicos Ghukas Karnetsi with prominent Armenian figures of India, bishops, contains rich material for studying the socio-economic situation of the Mother See of St. Echmiadzin, the spiritual life of the Armenian dioceses of India, the political situation in Eastern Armenia, etc. Some of the letters discuss the issues of the national liberation movement of the Armenian people and the liberation of Armenia from the Turkish-Persian yoke. The letters express the diversity of political views of different Armenian figures, their experiences and attitude to the political and religious problems of the Armenian people. The letters are interesting for studying the national liberation movement of the Armenian people. The letters also reflect the activities of the Catholicos of All Armenians in the field of education and printing. During the leadership of Ghukas Karnetsi, the decline and rise of the school in St. Etchmiadzin were due to a number of internal and external factors. During this period, the creation of cultural and educational institutions faced difficulties due to numerous economic, social and political problems. The correspondence contains rich material also for studying the construction activities of Karnetsi. The main building costs were covered by the famous Armenians of India. The Armenian community of India also financed the construction of the Cathedral of St. Etchmiadzin.
Keywords: Հայ եկեղեցու պատմություն